If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 10x = 3x + 19 Reorder the terms: 12 + 10x = 19 + 3x Solving 12 + 10x = 19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 10x + -3x = 19 + 3x + -3x Combine like terms: 10x + -3x = 7x 12 + 7x = 19 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 7x = 19 + 0 12 + 7x = 19 Add '-12' to each side of the equation. 12 + -12 + 7x = 19 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 19 + -12 7x = 19 + -12 Combine like terms: 19 + -12 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| 18x-5=7x+7 | | 12x+168=180 | | y+20+2y=-10-2y-15 | | -16+4=-4(x+7) | | 0.06(2t-3)=0.12(t+2)-0.42 | | 8-(2x-5)=3(x-1)-6 | | 7.31x+73.1=146.2 | | 64+2x=7x+16 | | 6x+15=3+8x-6 | | 3t^2-78t+480=0 | | H=80-16t^2 | | 12h+18-12h+18=(h+2) | | 2.9(x+2)-4=2.9x+1.9 | | 3(k-1)=2k+13 | | 3+(-87)+(-35)+(-74)= | | -5(3y-2)=-17y | | 2sec^2+Tan^2-3=0 | | 4a+2b=190 | | 7.7(x-2)=.3x+48.6 | | 3(4h+6)+2(-6+9)=(h+2) | | 11=1y-(-2) | | 6-6x-4=42+3x-10 | | (8+9x)=(8x+10) | | 2x^2+5x-361=0 | | 6x-(4x)=4 | | 9w+9=90 | | ln(7x-1)=-1 | | 4x-9=24x+6 | | 22=4(-3+5y)-2(1-8y) | | s+2.5s+20=62 | | -5y-6=-51 | | p^2+12p-40=5 |